Psychometric evaluation of the danish version of the electronic health literacy scale (eHEALS) in patients treated with percutaneous coronary intervention (PCI): A cross-sectional validation study. (2nd July 2022) - Palm, P; Brors, G; Borregaard, B; Rasmussen, T B; Helmark, C; Norekval, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: As many use the internet as a major source of health information, eHealth literacy has emerged as a potential concept for digital health care consumption. Therefore, healthcare professionals need to consider the eHealth literacy of patients when delivering health information to cardiac patients. Purpose: The aim of this study was to translate and evaluate the psychometric properties of the Danish version of the Electronic Health Literacy Scale (eHEALS) in a population of Danish PCI treated patients. Methods: The eHEALS was translated into Danish from the original English version, including forward translation, synthesis, backward translation and expert group consensus. The questionnaire was applied to a group of Danish PCI treated patients to be answered during hospital stay. Psychometric properties were assessed including internal consistency by Cronbach α, and confirmatory factor analysis (CFA) with a priori specified 1-, 2- and 3-factor models were performed to explore construct validity. Socio-demographic and patient-reported outcomes including health literacy, health-related internet use, and health status were collected to examine correlations with eHEALS scores. Results: A total of 1473 PCI treated patients were included in the analysis. The mean age was 66 years (SD 10.70) and more patients were males (n=1130, 78%). The mean value for the eHEALS score was 28.87 (SD 6.34), and the Cronbach α 0.94. The CFA indicated a good fit for three out of four of the goodness-of -fit indices. A mean difference on the eHEALS score between patients with the highest and lowest educational level was found to be 4.64 (95%CI, 2.43-6.85), p<0.0001. Strong correlations were observed between eHEALS scores and "ability to find good information"(r=0.636), "Understanding health information well enough to know what to do" (r=0.505), 'patients' perceived usefulness' (r= 0.650) and 'importance of using the internet' (r=0.621). Moderate correlations were observed to 'having used the internet to find information about health' (r=0.464), and "Appraisal of health information" (r=0.462), and weak correlations to self-rated physical health (r=0.119), self-rated mental health (r=0.110), and social support (r=0.207). Conclusion: The psychometric evaluation indicates that the Danish version of the eHEALS questionnaire is a valid instrument to measure eHealth literacy in patients treated with PCI, suggesting a multidimensional construct.